Characterization of strontium-rich groundwater in a typical alpine basin on Tibetan Plateau: Implications for sustainable exploitation and development - Shanhu Xiao; Jie Wang; Yong Xiao; Shaokang Yang; Yuqing Zhang; Jianhui Wang; Huizhu Chen; Wenxu Hu; Liwei Wang; Guangbin Zhu; Yanting Su; Dongyang Zhao (PLoS ONE, 2025)
This study focuses on mineral groundwater in alpine regions and its sustainable exploitation. The Tongde basin on Tibetan Plateau was investigated to reveal the hydrochemistry and formation of mineral groundwater in alpine basins and its sustainable development under anthropogenic disturbances. The results show that groundwater there is characterized by enriched strontium, with concentrations in the range of 0.29–2.03 mg/L, exceeding the mineral water threshold of 0.20 mg/L. Groundwater has large salinity variation but is predominantly fresh, with an average TDS of 456.72 mg/L and a dominant hydrochemical facies of HCO3-Ca. Groundwater chemistry is primarily governed by water-rock interactions, particularly silicates weathering, carbonates dissolution and cation exchange. The enriched Sr in groundwater primarily originate from the dissolution of silicate minerals and carbonate cements in arkosic sandstone and argillaceous siltstone, with albite, calcite, and strontianite being the primary minerals involved. Groundwater quality in the basin is mostly excellent to good, with EWQI values below 100. While agricultural practices have introduced nitrogen contaminants (NH4+, NO2- and NO3-) into groundwater. Among them, NO3- would pose potential health risks to various populations and should be addressed in the development of alpine basins with the endowment of mineral water resources.